Efficacy and Safety of Trastuzumab Emtansine in Her2 Positive Metastatic Breast Cancer: Real-World Experience. (9th August 2021) - Bahçeci, Aykut; Paydaş, Semra; Ak, Naziye; Ferhatoğlu, Ferhat; Saip, Pınar Mualla; Seydaoğlu, Gülşah; Bilici, Mehmet; Şimşek, Melih; Tekin, Salim Başol; Çalikuşu, Züleyha; Yavuz, Sinan; Şahin, Ahmet Bilgehan; et al.
Abstract: Aim: The aim of this study is to evaluate the efficacy and toxicity of trastuzumab emtansine (T-DM1) in cases with metastatic breast cancer (mBC) in different lines of treatment. Method: Retrospective analysis of T-DM1 results of human epidermal growth factor receptor 2 (Her2) positive 414 cases with mBC from 31 centers in Turkey. Findings: Except 2, all of the cases were female with a median age of 47. T-DM1 had been used as second-line therapy in 37.7% of the cases and the median number of T-DM1 cycles was 9. Progression-free survival (PFS) and overall survival (OS) times were different according to the line of treatment. The median OS was found as 43, 41, 46, 23 and 17 months for 1st, 2nd, 3rd, 4th and 5th line, respectively ( p = 0.032) while the median PFS was found as 37, 12, 8, 8 and 8 months, respectively ( p = 0.0001). Treatment was well tolerated by the patients. The most common grade 3–4 adverse effects were thrombocytopenia (2.7%) and increased serum gamma-glutamyl transferase (2%). Discussion: The best of our knowledge this is the largest real-life experience about the safety and efficacy of T-DM1 use in cases with mBC after progression of Her2 targeted treatment. This study suggests and supports that T-DM1 is more effective in earlier lines of treatment and is a reliable option for mBC.